Penerapan Algoritma C4.5 Dalam Mengklasifikasi Status Gizi Balita Pada Posyandu Desa Dames Damai Kabupaten Lombok Timur - Mahpuz Mahpuz; Amri Muliawan Nur; L M Samsu (Infotek: Jurnal Informatika dan Teknologi, 2022)
Nutrition is very important for human growth, especially in toddlers. Lack of or excess intake of nutrients in toddlers can affect nutritional status and health status. Children who have poor nutritional status will experience a decrease in body resistance and are susceptible to disease. The problem with Posyandu in Dames Damai Village is that toddler data reports are stored in a notebook containing toddler data along with the results of weighing which is carried out every month. However, the data only becomes a pile in the houses of the cadres. There is a need for data processing which will later produce useful information for the posyandu. The C4.5 algorithm is a classification technique used in this study which consists of 4 attributes used in the classification, namely gender, age, weight and height. The accuracy results obtained are very good or quite perfect, namely 97.02% while the AUC value obtained from the decision tree is 0.928